Desenvolvimento de uma ferramenta de apoio ao framework xPloiT em testes exploratórios - Salto, Leandro Keller (Universidade Federal de São Carlos, 2025)
This work demonstrates the restructuring of Spring Espresso, a web software created with the intention of assisting the application of the xPloiT framework in exploratory testing sessions in the context of games. Starting from a prototype developed by students of the Web Software Development 1 course at the Federal University of São Carlos, this application was created with the intention of serving as a support tool for xPloiT - a framework for conducting exploratory testing in games. The main evolution in relation to the initial prototype occurred in the restructuring of the class model, which was reorganized in order to offer a more consistent and aligned representation in relation to the framework. This restructuring enabled the integration of entities in a coherent way, resulting in a solid base to support future functionalities, although it is not free from limitations. The refactoring process revealed significant challenges, such as cascading impacts when modifying the previously established class relationship and structure, making it necessary to restart development to ensure robustness. It is concluded that this new version is better structured to support the application of the xPloiT methodology.
Development of a supporting tool for the xPloiT framework in exploratory testing
Keywords: Teste exploratório; Jogos digitais; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO; 9. Indústria, Inovação e Infraestrutura